ANTIOXIDANT, CYTOTOXICITY, AND STABILITY EVALUATION OF GINKGO BILOBA EXTRACT-BASED MICROEMULSIONS FOR ENHANCED THERAPEUTIC ACTIVITY - Singh, Manisha; Singh, Surya Pratap; R, Rachana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study is aimed to evaluate the antioxidant (AO) potential, cytotoxicity, and stability of preformulated Ginkgo biloba standard extractmicroemulsion (GBME), to investigate if, it retains the therapeutic potential of EGB761 and remains safe and stable for a longer period. Method and Results: GBME has shown enhanced AO (85.2±0.78%, IC50=31.3±0.45 μg/ml) in comparison to EGB761 (74.1±0.51%,IC50=49.4±0.05 μg/ml) using 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assay. Similarly, 2,2-diphenyl-1-picryl-hydrazyl-hydrate(DPPH) assay has also shown that AO for GBME (94.6±0.04%, IC50=11.4±1.03 μg/ml) was higher than EGB761 (78.6±1.20%, IC50=34.6±0.81 μg/ml).Further, IC50 value of antiradical unit of GBME was much lesser (ABTS=14.3±1.05 μg/ml and DPPH=17.03±1.8 μg/ml) in comparison to EGB761(ABTS=34.1±1.62 μg/ml and DPPH=37.5±0.08 μg/ml). Equivalently, both, hydrogen peroxide scavenging activity, and nitric oxide activity wereappreciably higher for GBME than the pure extract. The in vitro cytotoxicity assessment showed that GBME is quite safe (98.68±0.76% cell viability) incomparison to EGB761 (83.29±1.02%). Thereafter, these samples were tested for stability by evaluating their AO activity along with high-performanceliquid chromatography analysis, for the major phytocompounds, after 1 year, and results suggested that AO of GBME remained stable while comparingwith the freshly prepared GBME, whereas AO of EGB761 reduced significantly as compared to freshly taken EGB761 extract implying the degradationof phytocompounds supporting decrease in AO activity. Conclusion: Therefore, the observed results suggest that GBME maintained AO and scavenging activity along with enhanced shelf life with no observedtoxicity, which can be explored further for its potential therapeutic implications in various oxidative stress-induced central nervous system disorders.